Large genetic screens for gynogenesis and androgenesis haploid inducers in Arabidopsis thaliana failed to identify mutants - Portemer, Virginie; Renne, Charlotte; Guillebaux, Alexia; Mercier, Raphael (Frontiers in Plant Science, 2015)
Gynogenesis is a process in which the embryo genome originates exclusively from female origin, following embryogenesis stimulation by a male gamete. In contrast, androgenesis is the development of embryos that contain only the male nuclear genetic background. Both phenomena are of great interest in plant breeding as haploidisation is an efficient tool to reduce the length of breeding schemes to create varieties. Although few inducer lines have been described, the genetic control of these phenomena is poorly understood. We developed genetic screens to identify mutations that would induce gynogenesis or androgenesis in Arabidopsis thaliana. The ability of mutant pollen to induce either gynogenesis or androgenesis was tested by crossing mutagenized plants as males. Seedlings from these crosses were screened with recessive phenotypic markers, one genetically controlled by the female genome and another by the male genome. Positive and negative controls confirmed the unambiguous detection of both gynogenesis and androgenesis events. This strategy was applied to 1,666 EMS-mutagenised lines and 47 distant Arabidopsis strains. While an internal control suggested that the mutagenesis reached saturation, no gynogenesis or androgenesis inducer was found. However, spontaneous gynogenesis was observed at a frequency of 1/10,800. Altogether, these results suggest that no simple EMS-induced mutation in the male genome is able to induce gynogenesis or androgenesis in Arabidopsis.